Bubble mass transfer in fluids under gravity: a review of theoretical models and intensification technologies in industry - Ma, Yiyi; Guo, Linjiang; Xiao, Yuanhao; Ji, Anhua (Frontiers in Physics, 2024)
Bubble mass transfer is a common phenomenon in industrial applications. In this paper, bubble dynamics in both still and turbulent flow were introduced first, followed by the mass transfer properties of a single bubble and bubble swarms. Then, bubble mass transfer models for different scenarios were summarized, including three classical models, extended models, eddy diffusion and whirlpool theoretical models, and semi-or empirical correlations. Finally, existing methods for mass transfer intensification in industries were reviewed. Despite extensive research, the mechanism for bubble mass transfer has not been fully understood. Models are commonly limited to some specific conditions and the accuracy is limited, especially for bubble swarms and bubble mass transfer in turbulent and non-Newtonian fluids. Also, the mass transfer intensification methods have their own limitations. Additional exploration of knowledge on bubble mass transfer models and further improvement in mass transfer intensification technologies are still required in the future.